“I stand here, and I won’t move” - Grånemo, Maria (2021)
Forest work has traditionally been narrated from men’s perspectives and experiences. This research focus on women’s narratives from manual forest work in northern Swedish forest during the 20th century. During a time when major changes took place in both Swedish society and forestry enhanced work opportunities opened up in the forest for women in rural areas. I have interviewed 25 women who worked on planting, pre-commercial thinning and logging, and other forest work. Most women grew up in the rural parts of northern Sweden and were used to work from a young age. Many appreciated working outside in the forest and enjoyed the comradeship. The forest and forest work have strong connotations to masculinity and men’s labour. Women did not traditionally belong in this work sphere, especially not as a logger. As women they met challenges and resistance and had to have determination and stand up for themselves. But working in the forest also gave women a sense of freedom and personal satisfaction. The invisibility of women in historical documentation contributes to women’s role and their importance in history being forgotten. It further contributes to the reinforcement of forestry, in terms of both competence and labour, being considered best suited for men. This can further affect women’s attitude toward working within the forest industry today. My findings show that women, regardless of the male myth around forest work, are just as suitable, able and skilled to perform manual forest labour as anyone else.